Mini review of first-in-human integrin αvβ6 PET tracers - Kimura, Richard H.; Iagaru, Andrei; Guo, H. Henry (Frontiers in Nuclear Medicine, 2023)
This minireview of clinically-evaluated integrin αvβ6 PET-tracers reveals distinct differences in human-biodistribution patterns between linear peptides, including disulfide-stabilized formats, compared to head-to-tail cyclized peptides. All PET tracers mentioned in this minireview were able to delineate disease from normal tissues, but some αvβ6 PET tracers are better than others for particular clinical applications. Each αvβ6 PET tracer was validated for its ability to bind integrin αvβ6 with high affinity. However, all the head-to-tail cyclized peptide PET-tracers reviewed here did not accumulate in the GI-tract, in striking contrast to the linear and disulfide-bonded counterparts currently undergoing clinical evaluation in cancer, IPF and long COVID. Multiple independent investigators have reported the presence of β6 mRNA as well as αvβ6 protein in the GI-tract. Currently, there remains further need for biochemical, clinical, and structural data to satisfactorily explain the state-of-the-art in human αvβ6-imaging.